2010
DOI: 10.1007/s10067-010-1379-5
|View full text |Cite
|
Sign up to set email alerts
|

Group visits for rheumatoid arthritis patients: a pilot study

Abstract: This pilot study explored the feasibility of a group visit model for patients with rheumatoid arthritis (RA) and for medical staff at a private practice. RA patients were invited to attend six 3.5-h-long group visit sessions held once per month at a wellness center. Each included group discussion, individual patient examinations, interactive question, and answer periods, and topic-specific presentations from various health professionals. Nineteen of the 24 RA patients invited to the group visits agreed to atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“… L Kawasaki L et al [ 39 ] Willingness to attend group visits for hypertension treatment. M Shojania K, Ratzlaff M. [ 54 ] Group visits for rheumatoid arthritis patients: a pilot study. N Bray P et al [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“… L Kawasaki L et al [ 39 ] Willingness to attend group visits for hypertension treatment. M Shojania K, Ratzlaff M. [ 54 ] Group visits for rheumatoid arthritis patients: a pilot study. N Bray P et al [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Originally designed in the 1970s for primary care pediatrics, the GVM has been applied successfully in the care of myriad chronic diseases in adults, including obesity, headache, diabetes, and coronary artery disease . Group visits have repeatedly been shown to improve medication adherence, reduce urgent care and emergency room visits, and facilitate health education and anticipatory guidance, while at the same time greatly improving health care resource utilization and clinic efficiency .…”
mentioning
confidence: 99%
“…Real‐life experiences are strong advocates for behavioural changes and improved understanding of disease perspective and therapeutic interventions [30–32]. With regard to these aspects, a GMA could be superior to an IMA, especially in chronic patient care, which requires participants to deepen their knowledge of the disease and to improve adequate self management [17,24,33,34]. It has been suggested that GMAs may be especially effective in adolescents when they are offered according to their needs and requirements, as adolescents may be more sensitive to peers and group dynamics.…”
Section: Discussionmentioning
confidence: 99%